If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(y + -5) = 16 Reorder the terms: 4(-5 + y) = 16 (-5 * 4 + y * 4) = 16 (-20 + 4y) = 16 Solving -20 + 4y = 16 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 4y = 16 + 20 Combine like terms: -20 + 20 = 0 0 + 4y = 16 + 20 4y = 16 + 20 Combine like terms: 16 + 20 = 36 4y = 36 Divide each side by '4'. y = 9 Simplifying y = 9
| 13-(-7x)+5x-(-10)= | | 2x^2-5x-52=0 | | -8y+4=20 | | (4x+7)=(3x-5) | | 2x^4+2x^4=4x^4 | | 5x+10y=70 | | 5y+8(y-5)+9= | | 10y-2x+5y-10=180 | | 2=x+10 | | 65y-64y-51=13 | | 2x^4+2x^4-4x^4=0 | | -14v=-112 | | (4u+36)(u^2+4u-12)=0 | | 103-4x=32x+15 | | 7x*21x=9408 | | 17b=85 | | 10-7x=180-42x | | 3(2x-1)+4x=5(3x-2)+4 | | 6(2x-4)=2(4x-6) | | 3x=6x-7 | | x-12=5x | | 2a-3a+4a=5a-18 | | w/2-34/5=53 | | 9x^3+12x^2-45x= | | (2x-1)(2x-1)+5=4x(x-2)-2(2x+1) | | 4x^2-500x=0 | | 65=(3-2w)(w) | | 5g-4(-5-3g)=1-1g | | w/2-34=53 | | 2w^2-3w+65=0 | | m=(12-3)/(11+1) | | 9x-1=3+8x |